Comparison of the Conventional Dresden Protocol and Accelerated Protocol With Higher Ultraviolet Intensity in Corneal Collagen Cross-Linking for Keratoconus. Issue 5 (May 2017) - Choi, Moonjung; Kim, Jiwon; Kim, Eung Kweon; Seo, Kyoung Yul; Kim, Tae-im
Abstract : Purpose: To compare the accelerated corneal cross-linking (CXL) protocol and the conventional Dresden protocol in patients with keratoconus in terms of visual acuity, keratometric values, and topographic parameters. Methods: Twenty-eight eyes of 25 patients with primary keratoconus were divided into 2 groups; 15 eyes in group 1 received CXL under the standard Dresden protocol (3 mW/cm 2 for 30 min, dose 5.4 J/cm 2 ) and 13 eyes in group 2 were treated with the accelerated protocol (30 mW/cm 2 for 3 min 40 s, dose 6.6 J/cm 2 ). Visual acuity, refractive error, keratometry values obtained by both Pentacam and Auto Kerato-Refractometer, corneal thickness, and topometric indexes were compared 6 months postoperatively. Results: The visual acuity improved significantly from 0.17 ± 0.16 to 0.08 ± 0.09 logarithm of the minimum angle of resolution in group 1 ( P = 0.009). The cylindrical refractive error improved in both groups ( P = 0.05 in group 1 and P = 0.011 in group 2), and the spherical equivalent increased in group 1 ( P = 0.021). In group 1, the maximum keratometry value decreased by 0.55 ± 0.89 diopters ( P = 0.03), and the mean keratometry value decreased by 0.44 ± 0.63 diopters ( P = 0.017), whereas the changes in visual acuity, spherical and spherical equivalent refractive errors, and keratometric values in group 2 were not statistically significant. The corneal thickness at the apex decreased significantly in group 1 ( P = 0.001), but the change was not significant in group 2. Conclusions: Despite a higher UV dose (6.6 J/cm 2 ), accelerated CXL with higher UV intensity and reduced irradiation time showed a smaller topographic flattening effect than did the conventional Dresden protocol in primary keratoconus with documented progression.